The design and construction of a scanning probe nitrogen vacancy centre magnetometer - Tyler, Ashley (2021)
The isolated spin of the nitrogen-vacancy (NV) centre in diamond, which is formed from a vacancy and an adjacent nitrogen atom replacing carbon atoms in the diamond lattice, provides a highly promising system to realise non-invasive high-sensitivity magnetometry, even at room temperatures. The combination of the atomically sized detection volume, which for a single NV centre is defined by the spatial extent of the wavefunction, and high magnetic field sensitivity makes the NV centre a highly promising sensor to investigate magnetism on the nanoscale. In recent years NV centres have been used to produce 2D maps of magnetic fields with nanoscale resolution by affixing single or small numbers of NV centres to the very tip of a scanning probe. To date, scanning probe NV magnetometers have produced images with some of the smallest probe-sample distances seen in magnetic field sensing, with probe-sample distances of the order 50 nm routinely achieved.